THE IMPLEMENTATION OF BLINDFOLD GAME TO IMPROVE STUDENTS VOCABULARY MASTERY AT MTS PERCONTOHAN TEBING TINGGI - Rukmana Harahap, Anita (BRIGHT VISION Journal of Language and Education, 2023)
This research was aimed to improve the students’ vocabulary mastery by using blindfold games. The subjects of this study were 25 students at 10th grade in MTs Percontohan Tebing Tinggi in academic year 2019/2020. This research was conducted  by using  classroom action research that  consist  of two cycle.  The technique of analyzing data for quantitative data was the students’ score of test. While for qualitative data, the researcher used the technique by Miles and Huberman. The result of this research showed that the mean of the students score was 41.04 in which there were 2 or 8 % from 25 students who passed the standard minimum score or KKM. In the post test I there were 10 or 40 % who improve and the score mean was 68.48. Meanwhile in posttest II the mean score was 80.32. There were 23 students or 88% passed the standard minimum score. It indicated that blindfold game could improve the students’ vocabulary. This result is strength by the observation and the interview result that students were more active in the class and enjoy the learning process.